The Salvinorin Analogue, Ethoxymethyl Ether Salvinorin B, Promotes Remyelination in Preclinical Models of Multiple Sclerosis - Paton, Kelly F.; Robichon, Katharina; Templeton, Nikki; Denny, Lisa; Al Abadey, Afnan; Luo, Dan; Prisinzano, Thomas E.; La Flamme, Anne C.; Kivell, Bronwyn M. (Frontiers in Neurology, 2021)
Multiple sclerosis is a neurodegenerative disease associated with demyelination and neuroinflammation in the central nervous system. There is an urgent need to develop remyelinating therapies to better treat multiple sclerosis and other demyelinating diseases. The kappa opioid receptor (KOR) has been identified as a potential target for the development of remyelinating therapies; however, prototypical KOR agonists, such as U50,488 have side effects, which limit clinical use. In the current study, we investigated a Salvinorin A analog, ethoxymethyl ether Salvinorin B (EOM SalB) in two preclinical models of demyelination in C57BL/6J mice. We showed that in cellular assays EOM SalB was G-protein biased, an effect often correlated with fewer KOR-mediated side effects. In the experimental autoimmune encephalomyelitis model, we found that EOM SalB (0.1–0.3 mg/kg) effectively decreased disease severity in a KOR-dependent manner and led to a greater number of animals in recovery compared to U50,488 treatment. Furthermore, EOM SalB treatment decreased immune cell infiltration and increased myelin levels in the central nervous system. In the cuprizone-induced demyelination model, we showed that EOM SalB (0.3 mg/kg) administration led to an increase in the number of mature oligodendrocytes, the number of myelinated axons and the myelin thickness in the corpus callosum. Overall, EOM SalB was effective in two preclinical models of multiple sclerosis and demyelination, adding further evidence to show KOR agonists are a promising target for remyelinating therapies.